(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study was conducted to examine the attitudes towards learning of the students at the Faculty of Sports Sciences at Firat University. While the population of the study consisted of the students of the Faculty of Sports Sciences at Firat University, the sample of the study consisted of 290 randomly selected students from the Faculty of Sports Sciences at Firat University on the condition that the sample was limited to Elazığ. To examine the attitudes towards learning of the students participating in the study, a personal information form and the "Attitudes towards Learning Scale" were used.In conclusion, it was observed that the attitudes of the students studying at the faculty of sports sciences towards learning differed based on their gender, age, departments, grades, daily study hours, and weekly study hours in certain subscales and in the overall total. In some subscales, it was observed that there was no effect on their attitudes. Additionally, it was observed that family income status and the place of residence did not affect the attitudes of the students towards learning in all subscales and the overall total score of the scale.